DESIGN FEATURES STEEL CONCRETE DESIGNS (Municipal economy of cities (Technical science), 2013)
Reported in respect of theoretical and experimental investigations of steel concrete structures at different ways of longitudinal loads and shows the technical and economic efficiency of these structures instead of steel and concrete.